2011
DOI: 10.1002/lary.21332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features, health‐related quality of life, and adult voice in juvenile‐onset recurrent respiratory papillomatosis

Abstract: JORRP is a risk factor for permanent laryngeal pathology and voice-disturbances in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…However, six adult RRP patients (22%) revealed a normal voice quality (VHI total score < 20). The vast majority of the RRP population in northern Sweden (59%) experienced a moderate to severe voice dysfunction, while the remaining subjects reported minimal voice handicap, consistent with previous studies [18][19][20].…”
Section: Discussionsupporting
confidence: 85%
“…However, six adult RRP patients (22%) revealed a normal voice quality (VHI total score < 20). The vast majority of the RRP population in northern Sweden (59%) experienced a moderate to severe voice dysfunction, while the remaining subjects reported minimal voice handicap, consistent with previous studies [18][19][20].…”
Section: Discussionsupporting
confidence: 85%
“…The usefulness of this 15D instrument has been tested in oncologically treated head and neck cancer patients [8] as well as among benign head and neck conditions (juvenileonset recurrent respiratory papillomatosis, septoplasty, tonsillectomy) [17][18][19]. It enables comparisons between different health conditions as well as between general populations [12].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Although they still experienced significant voice problems, JoRRP patients reported only slightly lower QoL in their adult life. 8 Two studies in adults, including both JoRRP and AoRRP patients, confirmed that patients experience more voice problems than the general population. 9,10 Both studies showed that in particular, social functioning was impaired.…”
Section: Introductionmentioning
confidence: 88%
“…Two studies in children showed worse health‐related QoL, impaired social functioning, and lower psychosocial health status . Although they still experienced significant voice problems, JoRRP patients reported only slightly lower QoL in their adult life . Two studies in adults, including both JoRRP and AoRRP patients, confirmed that patients experience more voice problems than the general population .…”
Section: Introductionmentioning
confidence: 92%